The correlation of foreign language proficiency, employment and regional competitiveness in the North Great Plain Region of Hungary - Hajdú, Zita (Acta Agraria Debreceniensis, 2007)
Employment is one of the basic factors when evaluating a region’s competitiveness. Boosting employment figures will also increase individual income. However, the creation of jobs alone will not solve the problems of unemployment, as labour force with skills matched to labour market demands should also be available. Continuous development of the labour force, adjusted to recent needs in the labour market, can contribute to a region’s competitiveness. Mismatches between education and labour market requirements would be too expensive, especially for backward regions like the North Great Plain Region of Hungary. Foreign language education should also be adapted to the changing economy when selecting target languages and language skills. A workforce equipped with contemporary and needed second language skills can be an element in making a region attractive for investors. Although current trends show signs of improvement, Hungary and especially the North Great Plain Region still does not have much to offer in this respect. The paper examines the reasons for the low level of second language acquisition among Hungarians and the population of the North Great Plain Region and explores the ways foreign language knowledge could promote economic development.